Urdu Travelogues about Türkiye and the Turks During the Reign of Sultan Abdulhamid II. - Arzu CIFTSUREN; Zeynep Altınköprü (بازیافت, 2025)
The travelogues written in Urdu by travellers from the Indian subcontinent during the reign of Sultan Abdulhamid II offer valuable insights into the Ottoman Empire and Istanbul. These travelogues encompass detailed observations of the historical, cultural, social, and political aspects of Istanbul, Ottoman society, and the reign of Sultan Abdulhamid II. Commencing in the late nineteenth century, these travelogues evolved into a substantial repository for comprehending the social fabric, cultural values, and prominent figures of the era. The travellers' motivations for visiting the Ottoman lands were diverse, encompassing the fostering of coordination among Islamic countries, the opportunity to visit Istanbul, and the close study of Ottoman society. Among these figures, Nawab Omar Khan, Shibli Nomani, Molavi Abdurrahman Amritsari, Munshi Mahbub Alam, Shaikh Abdulqadir, and Nazli Rafia are particularly noteworthy. These individuals meticulously documented their observations of Ottoman social structures, educational systems, daily life, traditions, cultural values, and significant political figures. These travelogues provide a comprehensive portrayal of Ottoman society and present both positive and negative impressions of the period. They serve as invaluable sources for studying the cultural and social structure of the period and provide essential insights into the nature of the Ottoman Empire during the reign of Sultan Abdulhamid II. The travelogues make an important contribution to our understanding of the historical and social contexts of the late Ottoman period.